Application of Ultraviolet Spectrophotometry with Dual Wavelength Method for the Simultaneous Determination of Ecstasy Tablet Content - Marsaulina, Hutagaol Debora; M, Muchlisyam; Morin, Sinaga Siti (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: Ecstasy is a type of narcotic tablet and is very popularly used as a stimulant. The main content is Methylene dioxymetamphetamine (MDMA) and Methamphetamine (MA), but because a large amount of demand is not balanced with sufficient supply, ecstasy tablets are often adulterated with various contents, such as Paracetamol (PCT), Caffeine (KFN) and Ephedrine (EFD). Ecstasy tablets are often combined with other active compounds so that they can cause problems in determining the levels of tablets carried out in the Police Forensic Lab, so a cheaper, effective, and fast method is needed in determining the levels of these tablets. Methods: The research was conducted experimentally with the spectrophotometric method, namely the dual-wavelength method, then the validation was tested based on the validation parameters, namely linearity, accuracy, precision, LOD and LOQ. Then, this method was applied to determine levels of MA, EFD, KFN and PCT in tablet preparations. Results: The results showed that the application of the dual-wavelength method for the assay was carried out at λ 250.6 nm and 263 nm for KFN, at λ 263 nm and 281.8 nm for MA, at λ 259.4 nm and 255 nm for PCT at λ 255 nm and 236 nm for EFD, respectively. with a level result of 40.05; 1.63; 38.11; 20.21 for MA, EFD, KFN and PCT respectively, and with good precision and accuracy Conclusions: The dual-wavelength ultraviolet spectrophotometric method was successfully applied to determine the levels of MA, EFD, KFN and PCT mixtures in tablets. Keywords: methamphetamine, ephedrine, caffeine, paracetamol, dual wavelength method.